Using the analytic hierarchy process for selecting prototypes in the development process of fashion garment products - Moretti, Isabel Cristina; Braghini Junior, Aldo; Colmenero, João Carlos (Acta Scientiarum. Technology, 2017)
Â  To remain in the market, the process of development of fashion garment products produces a large quantity of products. During this process, the prototypes are made, evaluated and selected to compose the collection, thus the designers use some criteria to select them. For a designer, this process of selection is a complex decision-making, because they need to combine several criteria to attend a very specific target audience. Within this context, the main objective of this study was to propose a model for the selection of prototypes in the development process of fashion garment products, based on a multi-criteria tool, the Analytical Hierarchy Process (AHP). The model was developed based on literature, and the criteria used were: part acceptance, cost, design and production. Then, the developed tool was applied to a real case study and proved to be efficient, thereby enabling a structured modeling of the problem considering the multiple criteria and uncertainty. Â 